HUBUNGAN WAKTU TUNGGU PENDAFTARAN DENGAN KEPUASAN PASIEN DI TEMPAT PENDAFTARAN PASIEN RAWAT JALAN (TPPRJ) - Marice Simarmata; Balqis Wasliati Wasliati; Felix Kasim; Ira Cahyani Saragih (JURNAL KESMAS DAN GIZI (JKG), 2021)
Patient waiting time in service at Place Of Patient Outpatient Registration was one of the important factors that will determine the hospital's initial image. Patient waited time also becomes one of the potential components as the cause of dissatisfaction. If the waiting time in the old outpatient medical record then it will reduce patient comfort. This research aims to registration waiting time relationship with patient satisfaction in Outpatient Registration Place Grandmed of Hospital Lubukpakam 2017. In this paper type was observational cross-sectional study. The population in this research was the outpatient Outpatient Registration Place (TPPRJ) that 124 people were sampled by purposive sampling techniques, methods of data collection by interviewing indirectly by using a questionnaire, data analysis using Chi-square test. Based on the results of writing, it is known that the waiting time for registration in the fast category is 56.5%. Patient satisfaction in the satisfied category of 62.1%). There is a registration waiting time relationship with patient satisfaction in Outpatient Registration Place p-value (= 0.010) <Î± (= 0.05). Suggested for Outpatient Registration Place Officer Grandmed of Hospital Lubuk Pakam, should pay attention to the long waiting time at Outpatient Registration Place to work more quickly and precisely according to the SOP so that the patient always feel satisfied, happy with the services already provided by the clerk.